Dose planning in three-dimensional conformal radiation therapy (3D-CRT) manual - Sukhikh specialist in the field of nuclear energy Associate Professor of Tomsk Polytechnic University, Candidate of Physical and Mathematical Sciences; Sutygina specialist in the field of nuclear technologies engineer of Tomsk Polytechnic University; Stakhova specialist in the field of nuclear technologies engineer of Tomsk Polytechnic University; Sukhikh physicist Professor of Tomsk Polytechnic University, Doctor of Sciences (TPU Publishing House, 2023)
This manual provides an overview of the fundamentals of three-dimensional conformal radiation therapy (3D-CRT) treatment planning based on international recommendations used by cancer care clinics around the world. The manual consists of a concise theoretical foundation combined with a methodical description of practical aspects and procedures for the 3D-CRT treatment preparation and planning. Additionally, it offers methodological recommendations on radiation treatment planning for tumors of various locations using computer systems such as Monaco, PlanUNC which arc essential for laboratory work within the "Radiation Therapy Planning" and "Modern Radiation Therapy Methods" courses of study.